SI-PEKA : OPEN FINANCIAL MANAGEMENT INFORMATION SYSTEM AS AN EFFORT TO CONTROL INTERNAL FINANCIAL BUDGETS IN THE EDUCATIONAL ENVIRONMENT - Rafi, Muhammad; Lestari, Rika; Ayunda Pratiwi, Venni (Fakultas Ekonomi dan Bisnis Universitas Katolik Indonesia Atma Jaya, 2024)
The purpose of writing this article is to describe the concepts of a sound financial management information system, technology-based financial management, and an open financial management information system (SI-Peka). First, a healthy financial management information system is described by the good quality of financial statements and the acquisition of an unqualified opinion from the auditor. Second, technology-based financial management is one of the right solutions to control fraud in the education environment. Third, through the use of technology, a website can be created, namely SI-Peka, which integrates various information related to financial data in educational institutions or institutions with the aim of making it easier to supervise financial management and prevent the risks of fraud in financial reporting.